Spirobifluorenyl Phosphonic‐Based Ionic HOFs: Regulation Proton Transport and Single Crystal Superprotonic Conductivity - Cao, Xiao‐Jie; Cao, Li‐Hui; Chen, Xu‐Yong; Qi, Simeng; Zhou, Bin; Hou, Xiao‐Ying (Chinese journal of chemistry, 2025)
Comprehensive Summary The design of ionic hydrogen‐bonded organic frameworks (iHOFs) with single crystal superprotonic conductivity is of great significance for studying the mechanism of proton conduction materials at molecular level. To regulate the proton transport path, this study focused on using stereoscopic 2,2',7,7'‐tetraphosphone‐9,9'‐spirofluorene regulated by different lengths of amidine compound to form two chemically identical but structurally different single crystals iHOF‐46 and iHOF‐47. Both of them have hydrogen bond networks of different dimensions and highly anisotropic proton conductivity, and the clear proton transport path is proposed by analyzing the single crystal structure. Importantly, the experimental results show that iHOF‐47 with a two‐dimensional (2D) hydrogen bond network has a proton conductivity of up to 0.193 S·cm−1 in the (0, 0, –1) direction at 80 °C and 98% RH. A combination of single‐crystal structure analysis and density functional theory (DFT) calculations reveals that iHOF‐47 has a very continuous and smooth proton transport path in the direction of (0, 0, –1), and the lower energy barrier required for proton transport leads to higher proton conductivity. This is significant for guiding the unidirectional growth of crystals and establishing a "visible" proton conductivity pathway. In this paper, iHOF‐47 has a two‐dimensional layered hydrogen bond network, which is more conducive to plane transport, and continuous interlayer proton transport is the main conduction pathway. DFT calculations confirm that iHOF‐47 has a lower energy barrier in the (0, 0, –1) direction, a more continuous smooth proton transport path, and a superproton conductivity of up to 0.193 S·cm−1.